JOB SATISFACTION OF HIGH SCHOOL OF SOCIAL SCIENCE AND POLITICAL SCIENCES (STISIP) YAPIS WAMENA SCIENTIFIC SCIENCE BASED ON JOB SATISFACTION SCALE - Soltan Takdir; Muhammad Ali (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
Abstract This study aims to determine the level of job satisfaction of the employees of STISIP Amal Scientific Yapis Wamena based on the job satisfaction scale. Job satisfaction is an essential foundation in managing the organization to achieve the desired goals. This research is expected to serve as consideration and input to Foundations and Universities, especially STISIP Amal Scientific Yapis Wamena, in managing employees according to existing characteristics. The total population in this study was 47 permanent employees of the foundation; the sampling method used was using the purposive sampling technique, which in measuring job satisfaction was based on specific considerations so the total population was 29 people. The data collection tool used is a questionnaire using a Likert scale with the help of SPSS analysis. Based on the results of the calculation of job satisfaction scores in general, the job satisfaction of STISIP Amal Ilmiah Yapis Wamena employees is included in the category of high job satisfaction with a cumulative average value of 105.6 (72.9%) with the highest indicator description being satisfied with the job itself. With a cumulative average score of 110 (75.9%) in the category of increased job satisfaction, the supervisor indicator with a cumulative average score of 107.75 (74.3%) in the category of high job satisfaction, indicators for colleagues with an average score The cumulative average of 104.5 (72%) is in the category of high job satisfaction and the lowest is the salary indicator with a cumulative average value of 100.25 (69.1%) in the category of high job satisfaction. Keywords: work goals, Job Satisfaction Scale